ANALISIS PERUBAHAN KINERJA DAN STRUKTUR EKONOMI KABUPATEN SIDOARJO SEBELUM DAN SAAT TERJADINYA SEMBURAN LUMPUR LAPINDO - Sutikno, . (Jurnal Ekonomi Pembangunan, 2010)
This study aims to identify patterns of growth and structural change in the economic sector and to analyze the performance of economic sectors and social-economic impact of the â€œLumpur Lapindoâ€ on the area in Sidoarjo. Analyze to identify patterns of growth and contribution to economic sectors and the performance of economic sectors, thus are: Location Qoution, Ratio Analysis of Growth Models, and Analysis Overley. Based on the results of base analysis, the potential and performance the economic sector before and during the â€œLumpur Lapindoâ€ occurred, indicating that the amount of the basic sector and the potential sectors in the District of Porong, Tanggulangin, and Jabon decreased in the event of â€œLumpur Lapindoâ€. Based on the results of analysis of social-economic losses from the Lapindo mudflow, the following results are obtained. Lapindo mudflow incident has caused damage to property in the area around the blast center. Damaged assets consist of: 1) Land and buildings housing residents; 2) productive plants such as rice, sugarcane, and pulses; 3) Buildings and equipment; 4) infrastructure such as toll roads, electricity networks, irrigation networks, water network, telecommunications networks, gas pipelines, with total losses estimated at Rp 33.27 trillion.